Political Behavior of the Javanese Diaspora Community Born in Sumatra in Kuala Lumpur, Malaysia - Setiadi, Ozi; Andriani, Faricha; Septiana, Lisa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The political behavior of the Javanese-born Sumatran (Pujakesuma) community in Kuala Lumpur, Malaysia is able to color the political life in their home country. The Pujakesuma community does not have political affiliations, but their voices are very influential in political contestation. This study uses the theory of political behavior. While the research approach is qualitative. Data collection was carried out by means of semi-structured interviews, non-participatory observation and was carried out indirectly, and supplemented with literature data. This study shows that the political behavior of the Javanese-born Sumatran diaspora community in Malaysia is strongly influenced by the factors driving their political behavior. The factors driving this political behavior are friendship, family, and also economy. However, religion and culture are also additional driving factors. Furthermore, this means that the political behavior of the Javanese-born Sumatran is not limited to ethnocentrism or ethnic background.